2020
DOI: 10.18203/2394-6040.ijcmph20203391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of obesity among adolescent school children of North Kerala

Abstract: Background: Obesity has emerged as one of the major health problems in recent years. This increasing prevalence has implications in health issues in later parts of life. Life style factors and diet practices are the attributed factors to the development of obesity.Methods: This cross sectional study was conducted among 1011 adolescent school children in Kozhikode corporation area, Kerala, South India after getting necessary permissions. A semi structured questionnaire which contained questions related to socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study suggested that obesity was higher among those who watched television and mobile and suffered from sleeplessness. Obesity was associated with television viewing in many studies, and the more the duration of television watching, the higher the prevalence of obesity (Viswambharan et al 2020). A review by Mech et al (2016) also found that television viewing mediated the relationship between socioeconomic status and overweight and obesity in children (Gatjens et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggested that obesity was higher among those who watched television and mobile and suffered from sleeplessness. Obesity was associated with television viewing in many studies, and the more the duration of television watching, the higher the prevalence of obesity (Viswambharan et al 2020). A review by Mech et al (2016) also found that television viewing mediated the relationship between socioeconomic status and overweight and obesity in children (Gatjens et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent obesity is growing very fast and leads to a wide range of health issues regardless of weight during adulthood. It has become increasingly important to identify the risk factors predisposing to overweight and obesity from childhood onwards (Viswambharan et al 2020). Adolescence is a period of high physical growth and reproductive maturation that generally requires optimal macro or micronutrients or both (Egidaw and Gebremariam 2019;Kumar et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a well-planned curriculum and provision in school timetable, Physical and Health Education has been mostly neglected in the schools in the state of Kerala. This has resulted in an unprecedented hike in the percentage of obese and overweight children and adolescents, with current estimates at approximately 10% in Kerala (Nair & Chellappan, 2021; Viswambharan, Bina & Raphael, 2020; Abraham & Pillai, 2019) [7,13,1] . Decreased physical activity has been identified as a main cause of obesity in children and adolescents (Sallis et al, 2012) [10] .…”
Section: Introductionmentioning
confidence: 99%